Morphological and Stomata Characteristics of Trembesi (Samanea saman (Jacq.) Merr.) Leaves as Green Plants in Padang City, Indonesia - Vauzia Vauzia; Fadhila Mayandri; Nur Azizah; Rizka Putri Alti (Postgraduate, University of Mataram, 2023)
Greening along roads can be an alternative solution to overcome air pollution in urban areas. Direct contact of plants with pollutant particles in the air will affect the condition of plants, especially on leaves. Knowledge of morphological characteristics and stomata on leaves that have the potential to absorb pollutants is the basis for understanding plant responses to environmental changes. This research is descriptive research conducted in September-December 2021 with leaf samples taken in the area of ​​PT Semen Padang, Padang State University, and Andalas University forests. Data were analyzed by t test level of 5%. The results showed that the morphological characteristics of trembesi leaves in the PT Semen Padang and Padang State University areas had significant differences in the aspects of the number of leaflets, leaf length, leaf width, not significantly different in the length of the mother petiole and the number of leaf branch bones and the characteristics of the stomata did not show any difference which is evident from the aspect of stomata length and stomata density. The morphological characteristics of trembesi leaves in the Padang State University and Andalas University forests showed significant differences in the length of the mother petiole, the number of leaflets, and the number of leaf veins, there was no significant difference in leaf length and leaf width and showed a significant difference in the aspect of stomata length, but did not show a significant difference in terms of stomata density. Morphological characteristics of trembesi leaves in the PT Semen Padang area and Andalas University forest showed significant differences in the length of the mother petiole, number of leaflets, leaf length, leaf width, and number of leaf veins and did not show significant differences in terms of stomata length and stomata density.